The Effect of IT Governance on Internal Audit Quality - Hussein, Kifah Sami (International Journal of Applied Research and Sustainable Sciences, 2024)
Effective IT management is crucial for an organization's progress, and inefficient management can lead to system inefficiencies. IT governance ensures an organization's IT systems are functioning as intended, provides oversight of IT operations, and mitigates related risks. Despite its importance, there is a lack of research on the impact of ITG on internal audit role, particularly in the context of internal control. This study aims to fill this research gap by investigating the relationship between ITG characteristics and IAF within IAF. The research examines the link between ITG and IAF, as well as ITG's impact on internal control practices. The study analyzes survey responses from 414 internal auditors in Iraqi companies using a statistical method. The results demonstrate a strong association between IT knowledge, internal auditing responsibilities, the degree of strength of the IAF-IT relationship, and the effectiveness of ITG processes. Additionally, there is a significant association between IT audit abilities and ITG mechanisms. Also, effective overall controls are positively associated with well-capitalized ITG processes and a strong relationship between IAF and IT. This research extends the earlier work on the role of ITG in auditing and focuses on the crucial importance of ITG in the creation of effective IT systems.